Front Cover: Ligand Exchange Strategy for Tuning of Helicity Inversion Speeds of Dynamic Helical Tri(saloph) Metallocryptands (Chem. Eur. J. 12/2019). Issue 12 (4th February 2019) - Sakata, Yoko; Chiba, Shunsuke; Miyashita, Masato; Nabeshima, Tatsuya; Akine, Shigehisa
Abstract : A ligand exchange strategy was successfully utilized for tuning the response speeds of helicity induction and inversion of a metal‐containing helical structure. The helicity changes were driven by the exchange of six axial amine ligands that are introduced into the three Co 3+ centers in the metallocryptands, and the response speeds were efficiently controlled by using different combinations of the starting and entering amine ligands. More information can be found in the Communication by Shigehisa Akine et al. onpage 2962 .